Pembelajaran Saintifik melalui Metode Bercerita untuk Perkembangan Kognitif Anak RA Kelompok A Mambaul Ulum - Siti Fatimah (Al Hikmah: Indonesian Journal of Early Childhood Islamic Education (IJECIE), 2019)
This research aims to describe implementation of scientific learning through storytelling methods, methods/techniques of storytelling for cognitive development, supporting and inhibiting factors of implementing Scientific learning with the storytelling method. The method used in this research through interviews and observation and documentation. The results showed 1) The scientific approach in group A of RA Mambaul Ulum was good and was carried out in accordance with procedures and involved all five senses such as observing, asking questions, gathering information, processing information and communicating 2) The method used by teachers of group A of RA Mambaul Ulum by giving stories in accordance with the theme and always using the media and using interesting ways so that children are able to focus their attention on the teacher's story 3) Supporting factors were the program of the headmaster of RA related to increasing teacher capacity in storytelling which was routinely carried out by IGRA at the Sub-district. The inhibiting factors consisted of not all parents of students were able to do follow Up and became an example in supporting the cognitive development of children at home